Autogenic Relaxation as a Supportive Nursing Intervention in Type 2 Diabetes Mellitus: A Single-Patient Case Study - Hirdes Harlan Yuanto; Ahmad Rosuli; Fajri Andi Rahmawan; Novita Putri Lestari (STIKep PPNI Jawa Barat, 2026)
Background: Type 2 diabetes mellitus is often accompanied by unstable blood glucose levels and is closely related to daily self-care. Psychological stress may activate sympathetic and counter-regulatory hormonal responses that can worsen glycemic control, supporting stress management as one component of comprehensive diabetes care. Objective: This case study aimed to describe the application of autogenic relaxation as a supportive nursing intervention for a patient with type 2 diabetes mellitus and unstable blood glucose levels. Methods: A descriptive single-patient case study, reported with reference to the CARE guideline, was conducted in the Tawang Alun inpatient ward of Blambangan Banyuwangi Regional General Hospital in 2025. The case was selected because the patient had type 2 diabetes mellitus with hyperglycemia, symptoms of glucose instability, and willingness and ability to follow relaxation instructions. Nurse-guided autogenic relaxation was provided once daily for three consecutive days (10–15 minutes/session) using a consistent sequence. Blood glucose, subjective complaints, vital signs, peripheral perfusion, and wound condition were observed descriptively alongside insulin therapy, dietary management, glucose monitoring, wound care, and health education. Written informed consent for publication of anonymized clinical information was obtained from the patient. Formal research ethics approval was not sought because the report retrospectively describes routine, non-experimental nursing care; the intervention formed part of care and no additional research procedure was performed. Results: At the initial nursing assessment, the patient reported weakness, dizziness, thirst, nocturia, and tingling in both feet, with blood glucose of 378 mg/dL. Documented pre-/post-session values were 329/320 mg/dL (day 1), 303/296 mg/dL (day 2), and 160/150 mg/dL (day 3). These changes occurred during comprehensive inpatient care that included insulin, dietary management, wound care, education, and monitoring; therefore, the contribution of relaxation cannot be isolated. The patient reported feeling stronger and no longer dizzy by day 3. Conclusion: Autogenic relaxation was feasible and completed as a supportive nursing intervention in this single case. Effectiveness cannot be inferred from one uncontrolled case, and the observed improvement cannot be attributed to relaxation alone. Medication, dietary control, glucose monitoring, wound and foot care, education, and follow-up remain central to comprehensive diabetes management.